Effectiveness of Adherence-Focused Interventions and Contemporary Predictors of Treatment Success in Drug-Sensitive Tuberculosis in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis (2018–2023) - Moh. Khairul Hassan (Effectiveness of Adherence-Focused Interventions and Contemporary Predictors of Treatment Success in Drug-Sensitive Tuberculosis in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis (2018–2023), 2026)
Drug-sensitive tuberculosis (TB) treatment success in low- and middle-income countries (LMICs) has historically fallen short of the WHO's 85% benchmark. Predictors of treatment success are well described, but newer adherence-focused interventions, including digital tools introduced since 2018, have not been synthesized alongside contemporary evidence on predictors. Methods. A systematic review and meta-analysis followed PRISMA guidelines and covered the period from January 2018 to April 2023 across PubMed, ScienceDirect, EBSCOhost, Cochrane Library, and CINAHL. Eligible studies reported treatment success rates, predictors, or interventions for drug-sensitive TB in LMICs. Random-effects models yielded pooled odds ratios (ORs) and effect sizes (ESs) with 95% confidence intervals (CIs); heterogeneity was assessed using I². Risk of bias was appraised using the Joanna Briggs Institute (JBI) checklist. Results. Eighty-four studies met inclusion criteria (71 observational, 12 controlled interventional, 1 uncontrolled interventional), covering 806,664 participants. Pooled treatment success was 87.6%, exceeding the WHO benchmark. HIV-negative status (OR 2.05, 95% CI 1.76–2.39), new case status (OR 2.23, 1.88–2.63), directly observed therapy (DOTS) receipt (OR 2.93, 1.74–4.93), and absence of smoking or alcohol use were significantly associated with success; residence, TB site, and bacteriological confirmation were not. Five interventions significantly improved success rates: asynchronous video observed therapy (aVOT) (ES 17.99, 2.47–131.03), medication event monitoring systems (MEMS) (ES 3.55, 1.80–7.00), patient support groups (ES 2.15, 1.86–2.48), pharmaceutical care (ES 2.09, 1.01–4.34), and a modified drug regimen (ES 1.75, 1.05–2.92). Conclusion and Implications. This review confirms established predictors and provides the first quantitative synthesis of newer digital adherence interventions, aVOT and MEMS particularly, for drug-sensitive TB in LMICs. Feasibility of digital interventions should be weighed against local digital access and health infrastructure before scale-up. KEYWORDS: Developing Countries, Medication Adherence, Meta-Analysis, Systematic Review, Treatment Outcome, Tuberculosis